Analisis Dan Perancangan Sistem Informasi E-Learning Berbasis Web Menggunakan Metode Prototype Dengan Standar ISO/IEC 25010 (Studi Kasus: PT Teknologi Informatika Solusindo) - Khoirunnisa Khoirunnisa; Bagus Riyadi; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2026)
The rapid development of information and communication technology demands digital transformation across various organizations to maintain operational relevance and efficiency. PT Teknologi Informatika Solusindo faces significant administrative challenges in employee training management, where the processes of material distribution, assignment delivery, and competence monitoring are still conducted manually. This condition results in low time efficiency, a high risk of document loss, and a lack of transparency in periodic monitoring. This study aims to analyze, design, and implement a website-based e-learning information system as a strategic solution to optimize employee self-training management. The system development method applied is the prototype method, which allows the design process to run adaptively and iteratively based on user feedback. To ensure the quality of the resulting software, a final evaluation was conducted by referring to the ISO/IEC 25010 international quality standard, focusing on the characteristics of functional suitability, usability, reliability, and performance efficiency. The results indicate that the developed e-learning information system successfully integrates the entire training process into a single centralized digital platform. The implementation of this system is capable of mitigating manual administrative risks, facilitating learning material accessibility, and professionally enhancing the effectiveness and governance of the training program at PT Teknologi Informatika Solusindo.